Child protection medical service demonstration centers in approaching child abuse and neglect in Taiwan. Issue 44 (November 2016) - Chang, Yu-Ching; Huang, Jing-Long; Hsia, Shao-Hsuan; Lin, Kuang-Lin; Lee, En-Pei; Chou, I-Jun; Hsin, Yi-Chen; Lo, Fu-Song; Wu, Chang-Teng; Chiu, Cheng-Hsun; Wu, Han-Ping
Abstract : Abstract: Child abuse includes all forms of physical and emotional ill treatment, sexual abuse, neglect, and exploitation that results in actual or potential harm to the child's health, development, or dignity. In Taiwan, the Child Protection Medical Service Demonstration Center (CPMSDC) was established to protect children from abuse and neglect. We further analyzed and compared the trends and clinical characteristics of cases reported by CPMSDC to evaluate the function of CPMSDC in approaching child abuse and neglect in Taiwan. We prospectively recorded children with reported child abuse and neglect in a CPMSDC in a tertiary medical center from 2014 to 2015. Furthermore, we analyzed and compared age, gender, scene, identifying settings, time of visits, injury type, injury severity, hospital admission, hospitalization duration, and outcomes based on the different types of abuse and the different settings in which the abuse or neglect were identified. Of 361 child abuse cases (mean age 4.8 ± 5.36 years), the incidence was highest in 1- to 6-year-old children (n = 198, 54.85%). Physical abuse and neglect were predominant in males, while sexual abuse was predominant in females ( P < 0.001). Neglect was most common (n = 279, 75.85%), followed by physical (n = 56, 15.51%) and sexual abuse (n = 26, 7.2%). The most common identifying setting was the emergency department (n = 320, 88.64%), with neglect being most commonly reported. Head, neck, and facial injuries were more common in physically abused children than in neglected and sexual abused children ( P < 0.005), leading to longer hospitalization ( P = 0.042) and a higher Injury Severity Score ( P = 0.043). There were more skin injuries in neglect ( P < 0.001). The mortality rate was 2.49% (n = 9). The CPMSDC could enhance the ability, alertness, and inclination of professionals to identify suspected cases of child abuse, and to increase the rate of registry. Cases of physical abuse had a higher Injury Severity Score, longer duration of hospitalization, and more injuries of head, face, and neck compared with other types of abuse. The reported rate of neglect was highly elevated after the CPMSDC established during the study period. Recognition of neglect is not easy, but the consequent injury, especially asphyxia, may lead to mortality.